2019
DOI: 10.3390/molecules24010145
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Compounds Isolated from Ricinodendron heudelotii

Abstract: This study was designed to explore the in vitro anticancer effects of the bioactive compounds isolated from Ricinodendron heudelotii on selected cancer cell lines. The leaves of the plant were extracted with ethanol and partitioned in sequence with petroleum ether, ethyl acetate, and n-butanol. The ethyl acetate fraction was phytochemically studied using thin layer chromatography (TLC) and column chromatography (CC). Structural elucidation of pure compounds obtained from the ethyl acetate fraction was done usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Compound 10 showed two molecular ion peaks at m/z 634.9866 [M-H] - and 1271.1479 [2M-H] - . After 1 H NMR analysis, the molecular formula was deduced as C 27 H 24 O 18 and was identified as 1, 2, 6, tri- O -galloyl β-D-glucose ( Fig 5.10 )after comparing it with published literature [ 43 ]. Compound 11 showed two molecular ion peaks at m/z 953.5759 [M-H] - and 1907.0813 [2M-H] - .…”
Section: Resultsmentioning
confidence: 99%
“…Compound 10 showed two molecular ion peaks at m/z 634.9866 [M-H] - and 1271.1479 [2M-H] - . After 1 H NMR analysis, the molecular formula was deduced as C 27 H 24 O 18 and was identified as 1, 2, 6, tri- O -galloyl β-D-glucose ( Fig 5.10 )after comparing it with published literature [ 43 ]. Compound 11 showed two molecular ion peaks at m/z 953.5759 [M-H] - and 1907.0813 [2M-H] - .…”
Section: Resultsmentioning
confidence: 99%
“…Bioactive compounds which are naturally obtained from plants have been recognised for their therapeutic potential in the treatment of different types of cancers [18][19][20][21][22]. These According to the World Health Organization, the classification of haematological malignancies into different categories is based on the origin of the uncontrollably differentiating cell, the stage of disease development and clinical features of the condition [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive compounds which are naturally obtained from plants have been recognised for their therapeutic potential in the treatment of different types of cancers [18][19][20][21][22]. These naturally sourced products, which are sometimes referred to as herbs or traditional medicines, have been recognised for their roles as chemotherapeutic adjuvants [9,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The bark helps cure malaria, yellow fever, and dysentery and equally has diuretic functions [7]. Recently, we reported the antimicrobial effect of R. heudelotii extract [8] and the cytotoxic effect of isolated compounds from the leaf extract [9]. It was also reported that the leaf extract exhibited regulatory role on the toxicity of artemisinin when co-administered with artemisinin [10].…”
Section: Introductionmentioning
confidence: 99%